Techno-economic Analysis of Investment and Operation of Photovoltaic Panels under a Load Sharing Scheme - Sandy Yudhatama; Agus Ulinuha (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the techno-economic feasibility of the operational period of a 40 kWp on-grid Photovoltaic Panel with a load sharing scheme at Ella Skincare, focusing on technical analysis, investment and operational costs, and the potential for electricity cost savings. Methodology: This study used a quantitative method by analyzing energy consumption data and electricity bills over 6 months before and 6 months after installing the Photovoltaic Panel. The system used 60 Vertex TSM-DE21 panels and a Solis S5-GC50K inverter. The data were processed to calculate the Net Present Value (NPV), Return on Investment (ROI), Levelized Cost of Electricity (LCOE), and Payback Period (PP). Main Findings: The research results showed a 33.9% reduction in PLN electricity power consumption and more than 30% savings in electricity costs each month after the installation of the Photovoltaic Panel. Although the NPV had not yet exceeded the initial investment, the ROI reached 13.64% in the first year, indicating significant financial potential in the long term. Novelty/Originality of this Research: This study provides empirical evidence on the effectiveness of the load sharing scheme in improving efficiency and reducing operational electricity costs in the commercial sector. This study offers new insights into the investment feasibility of Photovoltaic Panels in Indonesia, particularly in the context of utilizing renewable energy to reduce dependence on conventional energy sources.